Analysis of the Implementation of PSAK 01 regarding the Presentation of Financial Reports at the Sherlina Oriflame Agent Marpoyan Pekanbaru - Afriani, Fri Sella (First Ciera Publisher, 2023)
This research is a qualitative descriptive study carried out at the Sherlina Oriflame Marpoyan agent in Pekanbaru. The aim of this research is to determine the presentation of the Sherlina Oriflame Marpoyan agent's financial statements and to determine whether the presentation of the Sherlina Oriflame Marpoyan agent's financial statements is in accordance with generally accepted accounting principles, especially PSAK. 01. The data collection methods used are interviews and documentation. In this research, we use documentation techniques on the financial statements of the Sherlina Oriflame Marpoyan agent to observe how the systematic presentation of the elements of the financial statements is in accordance with PSAK No. 01. The data analysis method used is: 1) In analyzing the data, the information that has been collected is analyzed using the comparative descriptive method, namely comparing the data that has been collected with relevant theories and then drawing a conclusion. 2) Descriptive research is a research method that aims to describe existing phenomena that are taking place now or in the past. 3) Descriptive research analysis is a form of research data analysis to test the generalization of research results based on one sample carried out by descriptive hypothesis testing. 4) Comparative analysis is a form of variable (data) analysis to determine the differences between two or more groups of data (variables). Based on the research results, it can be concluded that the financial statements of the Sherlina Oriflame agent Marpoyan Pekanbaru are not in accordance with PSAK No. 01, due to: caused by internal factors. Internal factors because the management believes that the financial reports that have been prepared so far can meet the annual reporting requirements, in other words, Sherlina members lack knowledge regarding PSAK No.01.